Dynamic, reversible oxidative addition of highly polar bonds to a transition metal - Bertermann, Ruediger; Boehnke, Julian; Braunschweig, Holger; Dewhurst, Rian D.; Kupfer, Thomas; Muessig, Jonas H.; Pentecost, Leanne; Radacki, Krzysztof; Sen, Sakya S.; Vargas, Alfredo (Journal of the American Chemical Society, 2016)
The combination of Pt complexes and indium trihalides leads to compounds that form equilibria in solution between their In X oxidative addition (OA) products (Pt indyl complexes) and their metal-only Lewis pair (MOLP) isomers (LnPt -> InX3). The position of the equilibria can be altered reversibly by changing the solvent, while the equilibria can be reversibly and irreversibly driven toward the MOLP products by addition of further donor ligands. The results mark the first observation of an equilibrium between MOLP and OA isomers, as well as the most polar bond ever observed to undergo reversible oxidative addition to a metal complex. In addition, we present the first structural characterization of MOLP and oxidative addition isomers of the same compound. The relative energies of the MOLP and OA isomers were calculated by DFT methods, and the possibility of solvent-mediated isomerization is discussed.